2021
DOI: 10.3389/fcimb.2021.661589
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing for Pathogenic Diagnosis and Antibiotic Management of Severe Community-Acquired Pneumonia in Immunocompromised Adults

Abstract: BackgroundMetagenomic next-generation sequencing (mNGS) is a promising technique for pathogens diagnosis. However, application of mNGS in immunocompromised adults with severe community-acquired pneumonia (SCAP) is relatively limited.MethodsWe retrospectively reviewed 23 immunocompromised and 21 immunocompetent SCAP patients with mNGS detection from April 2019 to December 2019. The performances of pathogenic diagnosis and subsequently antibiotic adjustment in immunocompromised SCAP patients were compared to imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Adjunctive use also involves diagnostic stewardship, and use with standard microbiology testing in select populations may be the most beneficial. The performance of NGS workflows is enhanced when samples from specific patient populations, such as those who are immunocompromised, are studied ( 26 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive use also involves diagnostic stewardship, and use with standard microbiology testing in select populations may be the most beneficial. The performance of NGS workflows is enhanced when samples from specific patient populations, such as those who are immunocompromised, are studied ( 26 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…More polymicrobial infections were found in immunocompromised patients in comparison with immunocompetent patients (20). Peng etc(6) reported that more than half of microbiologically con rmed pneumonia having mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic next-generation sequencing (mNGS) can directly identify the pathogens' sequences in clinical samples and has been applied in clinical infectious disease diagnostics including pneumonia (5)(6)(7). Here, we report a case of severe community-acquired pneumonia in a 53-year-old man, in which the conventional pathogen-detecting tests were all negative including legionella urinary antigen test, while a great amount of DNA (7,957 in a total of 21,977,576 sequences) and RNA (3,443 in a total of 12,763,560 sequences) sequences of Legionella gormanii in bronchoalveolar lavage fluid were identified by mNGS. After quinolones antibiotic therapy, the patient recovered.…”
Section: Introductionmentioning
confidence: 99%